Expressiveness and Nash equilibrium in iterated Boolean games - Gutierrez, J; Harrenstein, P; Perelli, G; Wooldridge, M (International Foundation for Autonomous Agents and Multiagent Systems, 2016)
We introduce and investigate a novel notion of expressiveness related to temporal logics and game theoretic properties of multi-agent systems. We focus on iterated Boolean games, where each agent